Comparison of the performance of aerosol sampling devices for measuring infectious SARS-CoV-2 aerosols - Ratnesar-Shumate, Shanna; Bohannon, Kyle; Williams, Gregory; Holland, Brian; Krause, Melissa; Green, Brian; Freeburger, Denise; Dabisch, Paul (Aerosol science and technology, 2021)
To assess the risk of aerosol transmission of SARS-CoV-2, measurements of the airborne viral concentrations in proximity to infected individuals, the persistence of the virus in aerosols, and the dose of the virus needed to cause infection following inhalation are required. For studies aimed at quantifying these parameters, an aerosol sampling device needs to be employed. A number of recent studies have reported the detection of both genetic material and infectious SARS-CoV-2 virus in air samples collected in clinical settings. Previous studies have demonstrated that the efficiency of different samplers for collection and preservation of the infectivity of microorganisms can vary as a function of the specific microorganism. In the present study, the performance of eight common low-flow aerosol sampling devices were compared for their ability to collect and preserve the infectivity of airborne SARS-CoV-2 contained in small particle aerosols. The influence of sampling duration on recovery of infectious virus was also evaluated. Similar concentrations of infectious SARS-CoV-2 were measured in aerosols for the majority of the samplers tested, with the exception of the midget impingers, which measured significantly lower concentrations of SARS-CoV-2. Additionally, in three of the four impingers tested, additional clean airflow through the device following collection of infectious virus resulted in a decrease of the infectious concentration of virus over time, suggesting that virus was being inactivated and these devices may not be suitable for sampling for long durations. Further, RNA copies in the samples over time did not correspond with the losses of infectious SARS-CoV-2 observed in the impingers samples. These data can be utilized to inform interpretation of current studies on the SARS-CoV-2 viral loads in air samples, as well as inform sampling device selection in future studies.